Voice Recording in second language outside the classroom: Process and product - Le, Thinh (Journal of NELTA, 2018)
In Vietnam, English is a foreign language. Therefore, students do not have many opportunities to practise speaking outside the classroom. Inside the classroom, teachers focus on teaching grammar explicitly. To enable students to practise their speaking skills, Facebook closed groups were employed as a learning platform. Seventeen students were asked to record their speech on suggested topics, post them on Facebook closed groups and comment on their friends’ works within six weeks. The first and final recordings were employed to analyse in terms of fluency and complexity. These students were also interviewed after the course. They supposed that voice recording enabled them to have opportunities to practise their speaking skills. The first and final recordings showed that students improved their fluency and lexical complexity but not for syntactic complexity.